Child Protection In Cases Of Physical Violence And Bullying That Occurs To School Children In Batam City - Ricky Bintang Perdana; Winsherly Tan; Abdurrakhman Alhakim (PALAR | PAKUAN LAW REVIEW, 2026)
Physical violence and bullying are actions carried out by individuals against other parties and have the potential to have various adverse impacts on the victim. This research is focused on assessing the protection of children in cases of physical violence and bullying that occurs in the school environment, as well as examining the effectiveness of policies and protection mechanisms that have been implemented. The impact of such violent practices not only affects the physical condition of children, but also has an impact on psychological aspects, social interactions, and academic achievements. Ideally, schools function as a safe and conducive educational space for children's development, but in reality there are still various cases of violence that have not been handled optimally. Therefore, it is necessary to have a comprehensive identification of the factors that cause violence, as well as the strategic role of schools, parents, and the government in building an effective child protection system that can accurately identify children's needs. This research is expected to contribute ideas in the formulation of prevention and handling efforts to create a safe, comfortable, and free learning environment from violent practices. The type of research carried out empirically, with data collection carried out through interviews with the relevant agencies, namely the Women's Empowerment and Child Protection Office which has authority in child protection. Keywords: Child Protection, Physical Violence, Bullying, School, Batam City, Children's Rights